Nghiên cứu ứng dụng zeolit analcime cho quá trình tẩy trắng bột giấy cơ học từ thân ngô bằng hydroperoxit - Hoàng, Phan Huy; Hữu, Ngô Văn (Vietnam Journal of Chemistry, 2015)
This study presented the synthesis of analcime zeolite particles and their application for peroxide bleaching of mechanical pulp. By adding of zeolite to bleaching slurry of mechanical pulp that containing transition metals would decrease the rate of metal catalysed decomposition of hydrogen peroxide. These zeolite particles also allowed relative high brightness of pulp with the increase of brightness of 12 % ISO after bleaching. Furthermore, the suitable conditions for peroxide bleaching of mechanical pulp such as hydrogen peroxide dosage, zeolite charge, temperature and bleaching time were determined through a series of experiments. This kind of zeolite showed the a potential for replacement of chelation agent (DTPA) and stabilizing agent (Na2SiO3) in traditional bleaching process that were criticized from an ecological point of view.